2021
DOI: 10.3390/sym13020178
|View full text |Cite
|
Sign up to set email alerts
|

Solid Particle Erosion Area of Rotor Blades: Application on Small-Size Unmanned Helicopters

Abstract: Rotor blades play an important role in unmanned helicopters, and it is of great significance to study the erosion of rotor blades. In this study, titanium alloy (Ti-4Al-1.5Mn) was used as the helicopter rotor blades’ surface material. The commercial software Ansys-Fluent 18.0 was mainly used to study the erosion of solid particles on the helicopter rotor blades. The moving mesh method and the discrete phase method (DPM) were used to construct an erosion model of the blades at different speeds (500, 1000, or 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Liu [19] used the DPM model to simulate erosion of particles on turbine blades, and found that capture efficiency of blades increases firstly and then decreases with particle size. Yao [20] employed the same method and suggested that as particle mass flow increases, the DPM erosion rate of blade increases significantly. Noon and Kim [21] explored the impact of different concentrations of sediment particles on the performance of Francis turbine and found that as the concentration increases, the efficiency loss of Francis turbine also increases.…”
Section: Figure 1 Process Of Closed Brayton Cyclementioning
confidence: 99%
“…Liu [19] used the DPM model to simulate erosion of particles on turbine blades, and found that capture efficiency of blades increases firstly and then decreases with particle size. Yao [20] employed the same method and suggested that as particle mass flow increases, the DPM erosion rate of blade increases significantly. Noon and Kim [21] explored the impact of different concentrations of sediment particles on the performance of Francis turbine and found that as the concentration increases, the efficiency loss of Francis turbine also increases.…”
Section: Figure 1 Process Of Closed Brayton Cyclementioning
confidence: 99%
“…A similar study by Özen and Gedikli [17] investigated experimentally and numerically the solid particle erosion behaviors of helicopter rotor blades covered with Ti-6Al-4V, SS304, Al6061-T6, and Ni materials. Yao et al [18] used the ANSYS-Fluent software to study the solid particle erosion wear behavior of rotor blades made up of Ti alloy at different rotational speeds and particle flow rates. On the other hand, it has been numerically demonstrated in another study that erosion protection coatings can cause a reduction in the aerodynamic efficiency of the rotor [19].…”
Section: Introductionmentioning
confidence: 99%
“…1 The impact of erosion on the reliability of machine elements and high wear costs are broadly recognized. 2 It is commonly seen in oil pipelines, 3 rotor blades of helicopters, [4][5][6] blades of pumps that transfer liquid, 7 wind turbines, 8,9 and high-speed vehicles, especially aircrafts. 10 In commercial aircrafts, it is seen in radomes, cockpit windows, the leading edge of the wings, horizontal and vertical stabilizers, and gas turbines.…”
Section: Introductionmentioning
confidence: 99%